BIBLIOMETRIC ANALYSIS OF RESEARCH DEVELOPMENTS IN THE FIELD OF PUBLIC ADMINISTRATION - Nurhadi, Nurhadi; Meilinda, Selvi Diana (Journal of Research in Social Science and Humanities, 2024)
The development of science which is essentially towards the process of improvement will continue throughout the human thought process. This also occurs in the paradigm of public administration development so that it attracts the attention of researchers to analyze the development of public administration research. In this study using bibliometric analysis to describe the results of journal publications with data search tools using Publish or Perish produced 996 meta data and analysis tools using Microsoft Excel, and VosViewer to visualize meta data. The results showed that from 996 meta data with the keyword "paradigm of public administration development" obtained a publication range from 1995-2024, with the most documents being the type of book file published on books. google.com with a total of 83 book titles and the highest publication development trend occurred in 2020 with 129 publications while the results of network mapping using VosViewer obtained 4 authors, namely Ismail, I; Sos, S; Irawan B; Larasati, E. which is the most productive author in the field of public administration development paradigms. The research development map using VosViewer is grouped into 5 clusters. Fluctuating research shows that the paradigm of public administration development is a research topic that attracts researchers to write, study, and analyze the topic of the paradigm of public administration development so that the implications of this research are to help other researchers to further study the development of the paradigm of public administration and be associated with the latest phenomena.